Material Characteristics and Equalized Charging Control of New Lithium Cell for Battery Electric Vehicle - Yaya Wang, Juanjuan Wang (Forest Chemicals Review)
The purpose is to enable the lithium cell to realize rapid charging, and solve the battery safety problems caused by functional materials in the process of charging and power consumption, so that the lithium cell can be widely used in battery electric vehicles (BEV) to meet the needs of consumers. First, based on the intelligent material performance and working principle of the new lithium battery, the influence of different material processing on the performance of lithium cell is analyzed. Next, an equalized charging control system based on fuzzy control is created. Finally, according to different electrolytes, the thermal performance of new lithium cell of BEV and the performance of lithium cell are tested under equalized control. With the increase of temperature, the mass fraction loss of new lithium cell with silicon dioxide as the electrolyte is greater than that with fluoropolyimide as the electrolyte. Lithium cells with different electrolytes of silica dioxide and fluoropolyimide have good thermal stability. In the process of charging without equalized control, different single cells of BEV’s new lithium cell cannot be fully charged simultaneously. If continuous charging is conducted, the battery will be overloaded and then damaged. If the charging is stopped, the battery will be used for a short time in the process of recycling. When the equalized charging control system based on fuzzy control is used for equalized charging control, five single batteries in the lithium cell are filled successively around 900s. Therefore, the equalized charging control system based on fuzzy control can make the single charge state of lithium cell consistent, and there is basically no overcharge, which can protect the service time of BEV’s new lithium cell. This exploration has certain research significance for the thermal properties of electrolyte materials of BEV’s new lithium cell and the equalized charging of lithium cell.